Mesenchymal Stem Cell-Derived Extracellular Vesicles Promote Angiogenesis: Potencial Clinical Application - Merino-González, Consuelo; Zuñiga, Felipe A.; Escudero, Carlos; Ormazabal, Valeska; Reyes, Camila; Nova-Lamperti, Estefanía; Salomón, Carlos; Aguayo, Claudio (Frontiers in Physiology, 2016)
Mesenchymal stem cells (MSCs) are adult multipotent stem cells that are able to differentiate into multiple specialized cell types including osteocytes, adipocytes and chondrocytes. MSCs exert different functions in the body and have recently been predicted to have a major clinical/therapeutic potential. However, the mechanisms of self-renewal and tissue regeneration are not completely understood. It has been shown that the biological effect depends mainly on its paracrine action. Furthermore, it has been reported that the secretion of soluble factors and the release of extracellular vesicles, such as exosomes, could mediate the cellular communication to induce cell-differentiation/self-renewal. This review provides an overview of MSC-derived exosomes in promoting angiogenicity and of the clinical relevance for these cells in a therapeutic approach.